Prevention and treatment of symptoms associated with indwelling ureteral stents: A systematic review. (25th February 2017) - Betschart, Patrick; Zumstein, Valentin; Piller, Alberto; Schmid, Hans‐Peter; Abt, Dominik
Abstract: Temporary drainage of the upper urinary tract by internal ureteral stents is a routine procedure in endourology. However, it is associated with a clear side‐effect profile. Our aim was to evaluate prevention and treatment options of stent‐related symptoms. We carried out a systematic review according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis guidelines using MEDLINE and SCOPUS, and identified 107 appropriate records. A high number of these studies showed clear methodological limitations. Available data clearly support the use of α1 ‐blockers in patients suffering from stent‐related symptoms. It seems that antimuscarinic monotherapy or combination with α1 ‐blockers might also play an important role, whereas the use of classical analgesics in the treatment of stent‐related symptoms has not been assessed systematically within clinical trials so far. Improvements in stent design and material seem to have the potential to reduce stent‐related symptoms. However, so far there is no type of stent with outstanding characteristics and clear evidence suggesting fundamental advantages compared with a standard double pigtail stent. Although stent diameter does not seem to influence patients' comfort, it seems to be beneficial to choose a proper stent‐length. Coated and drug‐eluting stents, as well as intravesical drug application, seem to be promising concepts to prevent stent‐related symptoms, but still have to be considered as experimental approaches. Furthermore, thorough patient education has the potential to reduce the morbidity associated with ureteral stenting. Further research in the field seems to be mandatory.